2013
DOI: 10.1158/0008-5472.can-13-0158
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-515-5p by the Estrogen Receptor Modulates Sphingosine Kinase 1 and Breast Cancer Cell Proliferation

Abstract: Sphingosine kinase 1 (SK1) plays an important role in estrogen-dependent breast tumorigenesis, but its regulation is poorly understood. A subset of microRNAs (miRNA, miR) is regulated by estrogen and contributes to cellular proliferation and cancer progression. Here, we describe that miR-515-5p is transcriptionally repressed by estrogen receptor a (ERa) and functions as a tumor suppressor in breast cancer. Its downregulation enhances cell proliferation and estrogen-dependent SK1 activity, mediated by a reducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 33 publications
4
60
0
1
Order By: Relevance
“…However, recently, we identified its role as a tumour suppressor in breast cancer 11. We demonstrated that miR‐515‐5p transcription was directly down‐regulated by the oestrogen receptor and that miR‐515‐5p inhibited breast cell proliferation by inducing apoptosis 11. During this work, a change in MCF‐7 and MDA‐MB‐231 cell morphology was also observed, a finding that we investigate further here.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…However, recently, we identified its role as a tumour suppressor in breast cancer 11. We demonstrated that miR‐515‐5p transcription was directly down‐regulated by the oestrogen receptor and that miR‐515‐5p inhibited breast cell proliferation by inducing apoptosis 11. During this work, a change in MCF‐7 and MDA‐MB‐231 cell morphology was also observed, a finding that we investigate further here.…”
Section: Introductionsupporting
confidence: 57%
“…Both MCF7 and MDA‐MB‐231 cells appeared enlarged with a loss of polarity that is often associated with non‐migratory cells. This change did not correlate with the onset of cell death downstream of this miRNA 11 indicating that the effects of miR‐515‐5p on cell morphology may be caused by distinct targets and, consequently, through different signalling pathways. Additionally, because MDA‐MB‐231 is an ER‐negative breast cancer cell line, we propose that the oestrogen receptor‐α is not involved in these effects.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…miRNAs are short approximately 19-24 nucleotide non-coding RNA molecules that post-transcriptionally regulate gene expression via mRNA binding (RNA interference). In cancers, miRNAs have been shown to affect several key oncogenic processes including apoptosis, migration and proliferation (Fonseca-Sanchez et al 2013, Huang et al 2013, Pinho et al 2013. Interestingly, widespread dysregulation of miRNAs has been observed in prostate cancer (Schaefer et al 2010, Fendler et al 2011, Wach et al 2012, and these molecules have potential as both biomarkers and therapeutic targets/treatments (Lichner et al 2013, Maugeri-Sacca et al 2013.…”
Section: Introductionmentioning
confidence: 99%